THE INFLUENCE OF HOME CARE SERVICES ON THE QUALITY OF LIFE OF THE ELDERLY (PANGEEA, 2025)
The rapid aging of the global population, dominated by earlier onset of disease and longer life expectancy with conditions, generates major challenges in the field of geriatric healthcare. Community home aged care services are a viable alternative for providing care for the elderly and protect their health. The desire of the elderly to "age in place" can be satisfied by using a community-based model of home-aged care, which succeeds in reducing the stress of family care of the elderly, lowers the cost of long-term care and diminishes the financial burden of the government. Home care services reflect this emerging preference, allowing the elderly to remain with family members rather than accessing care services in an institutionalized system [1].Keywords: elderly; quality of life; healthy aging; home-based care service; caregiver;
Keywords: elderly; quality of life; healthy aging; home-based care service; caregiver